Soziale Marktwirtschaft : ein Modell für Europa ; Festschrift für Gernot Gutmann zum 65. Geburtstag - Klein, Werner 1930- Hrsg; Gutmann, Gernot 1929-2024 GefeierteR; Paraskewopoulos, Spiridon 1942- Hrsg; Winter, Helmut 1941-2017 Hrsg (Volkswirtschaftliche Schriften, 1994)
Lit.